Positive electrode active material and manufacturing method for the same, positive electrode including the same, and lithium secondary battery
Patent Information
- Application Number
- JP2024144044
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-08-24
- Filing Date
- 2024-08-26
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-08-26
AI Technical Summary
【0009】 一実施形態による正極活物質は、生産価格を最小化すると共に、容量を極大化したものであって、長寿命特性が確保され、高電圧での特性と高温特性が改善される。前記正極活物質を適用したリチウム二次電池は、高電圧使用条件でも高い初期充放電容量および効率を示すことができ、長寿命特性を達成することができ、高電圧および高温使用によるガス発生の問題が効果的に抑制され得る。
Smart Images

Figure 2025031698000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a positive electrode active material and a method for producing the same, a positive electrode containing the same, and a lithium secondary battery. [Background technology]
[0002] Lithium secondary batteries, which have high energy density and are easy to carry, are mainly used as the driving power source for mobile information terminals such as mobile phones, notebook computers, and smartphones. Recently, active research has been conducted on using high-energy-density lithium secondary batteries as driving power sources or power storage power sources for hybrid and electric vehicles.
[0003] In order to realize a lithium secondary battery suitable for such applications, various positive electrode active materials have been studied. Among them, lithium nickel oxide, lithium nickel manganese cobalt composite oxide, lithium nickel cobalt aluminum composite oxide, lithium cobalt oxide, etc. are mainly used as positive electrode active materials. However, while the demand for large-sized, high-capacity, or high-energy density lithium secondary batteries has recently increased sharply, it is expected that the supply of positive electrode active materials containing cobalt, a rare metal, will be extremely short. In other words, since cobalt is expensive and the remaining reserves are not large, there is a need to develop a positive electrode active material that excludes cobalt or has a reduced cobalt content. Summary of the Invention [Problem to be solved by the invention]
[0004] The present invention provides a positive electrode active material containing a lithium nickel-manganese composite oxide, which is economical, has high capacity, and has long life characteristics, and has improved high voltage characteristics and high temperature characteristics; a method for producing the positive electrode active material; and a positive electrode and a lithium secondary battery containing the positive electrode active material. [Means for solving the problem]
[0005] In one embodiment, a positive electrode active material is provided, comprising: a core particle containing a layered lithium nickel-manganese composite oxide; a first coating layer located on the surface of the core particle and containing Al; and a second coating layer located on the first coating layer and containing Mn.
[0006] In another embodiment, a method for producing a positive electrode active material includes: mixing a layered nickel-manganese composite hydroxide and a lithium source, performing a first heat treatment to obtain a lithium nickel-manganese composite oxide; adding an Al source to an aqueous solvent, adding and mixing the lithium nickel-manganese composite oxide, adding and mixing a Mn source, drying the mixture, and performing a second heat treatment.
[0007] In another embodiment, a positive electrode is provided that includes a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector, the positive electrode active material layer including the positive electrode active material described above.
[0008] In another embodiment, a lithium secondary battery is provided that includes the positive electrode, the negative electrode, and an electrolyte. Effect of the Invention
[0009] The positive electrode active material according to one embodiment minimizes production costs while maximizing capacity, ensures long life characteristics, and improves high voltage and high temperature characteristics. A lithium secondary battery using the positive electrode active material can exhibit high initial charge / discharge capacity and efficiency even under high voltage operating conditions, achieve long life characteristics, and effectively suppress problems with gas generation due to high voltage and high temperature use. [Brief description of the drawings]
[0010] [Figure 1] 1 is a cross-sectional view illustrating a lithium secondary battery according to an embodiment. [Diagram 2] 1 is a cross-sectional view illustrating a lithium secondary battery according to an embodiment. [Diagram 3] 1 is a cross-sectional view illustrating a lithium secondary battery according to an embodiment. [Figure 4] 1 is a cross-sectional view illustrating a lithium secondary battery according to an embodiment. [Diagram 5] 1 is a SEM-EDS image of a cross section of the positive electrode active material of Example 1, in which Mn is highlighted. [Figure 6] 1 is a SEM-EDS image of a cross section of the positive electrode active material of Example 1, in which Al is highlighted. [Figure 7] 1 is an HR-STEM image of a cross section of the positive electrode active material of Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention will be described in detail below so that those skilled in the art can easily implement the present invention. However, the present invention may be embodied in many different forms and is not limited to the embodiments set forth herein.
[0012] The terms used herein are merely used to describe exemplary embodiments and are not intended to limit the present invention. A singular expression includes a plural expression unless otherwise clearly indicated in the context.
[0013] As used herein, "combinations thereof" refers to mixtures, laminates, composites, copolymers, alloys, blends, reaction products, and the like of compositions.
[0014] It should be understood that the terms "including," "comprising," or "having" are intended to specify the presence of embodied features, numerals, steps, components, or combinations thereof, but do not preclude the presence or additional possibility of one or more other features, numerals, steps, components, or combinations thereof.
[0015] In the drawings, the thickness of layers and regions is exaggerated to clearly show them, and similar parts are designated by the same reference numerals throughout the specification. When a part such as a layer, film, region, or plate is said to be "on" another part, this includes not only the case where the part is "directly on" the other part, but also the case where there is another part between them. Conversely, when a part is said to be "directly on" the other part, it means that there is no other part between them.
[0016] Here, the term "layer" includes not only shapes formed on the entire surface when observed in a plan view, but also shapes formed on a portion of the surface.
[0017] The average particle size can be measured by methods well known to those skilled in the art, for example, by using a particle size analyzer, or by using a transmission electron microscope image or a scanning electron microscope image. Alternatively, it can be measured using a dynamic light scattering method, and data analysis can be performed to count the number of particles for each particle size range, and the average particle size can be calculated based on the result. Unless otherwise defined, the average particle size is the diameter (D 50 In addition, unless otherwise defined, the average particle size is determined by measuring the size (diameter or major axis length) of 20 or more randomly selected particles in a scanning electron microscope image to obtain a particle size distribution, and calculating the diameter (D 50 ) may be taken as the average particle size.
[0018] Here, "or" is not to be construed as exclusive; for example, "A or B" is to be construed as including A, B, A+B, etc.
[0019] The term "metal" is understood to include general metals, transition metals, and metalloids (semimetals).
[0020] positive electrode active material In one embodiment, a positive electrode active material is provided, comprising: a core particle containing a layered lithium nickel-manganese composite oxide; a first coating layer located on the surface of the core particle and containing Al; and a second coating layer located on the first coating layer and containing Mn.
[0021] Recently, as the price of cobalt, a rare metal, has soared, there is a demand for the development of positive electrode active materials that exclude cobalt or reduce its content. Among them, positive electrode active materials with olivine crystal structures such as lithium iron phosphate (LFP), lithium manganese phosphate (LMP), and lithium manganese iron phosphate (LMFP), or spinel crystal structures such as lithium manganese oxide (LMO), have a limited capacity to realize high capacity due to the small amount of lithium that can be utilized within the structure. Layered nickel-manganese positive electrode active materials have a high amount of lithium available within the structure and are suitable as materials for high-capacity batteries because they have excellent capacity and efficiency characteristics. However, the removal of cobalt, which plays a key role in the layered structure, reduces structural stability, increases resistance, and makes it difficult to ensure long life characteristics. In addition, the removal of cobalt accelerates side reactions between the positive electrode active material and the electrolyte under high voltage and high temperature conditions, increasing the amount of gas generated and reducing life characteristics.
[0022] In one embodiment, a cathode active material is proposed that can maximize capacity and efficiency by introducing a first coating layer and a second coating layer to a layered lithium nickel-manganese composite oxide core particle, and can reduce gas generation even under high voltage and high temperature conditions, thereby realizing long life characteristics.
[0023] Core Particles The core particle includes a lithium nickel-manganese composite oxide. The nickel content may be 60 mol% or more with respect to 100 mol% of all metals excluding lithium in the lithium nickel-manganese composite oxide, and may be, for example, 60 mol% to 80 mol%, 65 mol% to 80 mol%, 70 mol% to 80 mol%, 60 mol% to 79 mol%, 60 mol% to 78 mol%, or 60 mol% to 75 mol%, etc. When the nickel content satisfies the above range, a high capacity can be realized, and structural safety can be improved even if the cobalt content is reduced.
[0024] The manganese content may be, for example, 10 mol % or more relative to 100 mol % of all metals excluding lithium in a lithium nickel-manganese composite oxide, such as 10 mol % to 40 mol %, 15 mol % to 35 mol %, 15 mol % to 30 mol %, or 20 mol % to 30 mol %, etc. When the manganese content satisfies the above range, the positive electrode active material can achieve high capacity while improving structural stability.
[0025] The lithium nickel-manganese composite oxide may be, for example, a lithium nickel-manganese-aluminum composite oxide further containing aluminum in addition to nickel and manganese. When the composite oxide contains aluminum, it is advantageous to maintain a stable layered structure even if the cobalt element is excluded from the structure. The content of aluminum relative to 100 mol% of the lithium nickel-manganese-aluminum composite oxide may be 0.1 mol% or more, 0.5 mol% or more, or 1 mol% or more, for example, 1 mol% to 3 mol%, 1 mol% to 2.5 mol%, 1 mol% to 2 mol%, or 1.5 mol% to 2.5 mol%. When the aluminum content satisfies the above range, a stable layered structure can be maintained even if cobalt is excluded, and the problem of the structure collapsing due to charging and discharging can be suppressed, and the long life characteristics of the positive electrode active material can be realized.
[0026] According to one embodiment, the aluminum concentration in the core particle may be uniform. That is, the aluminum concentration in the core particle may be uniformly distributed from the center to the surface, or the aluminum concentration in the core particle may be higher or lower than that in the inside, and the aluminum may be uniformly dispersed in the core particle. This may be a structure obtained by synthesizing a composite oxide using nickel-manganese-aluminum hydroxide as a precursor by using an aluminum raw material in the preparation of a precursor without additionally doping aluminum during the synthesis of the core particle. The core particle may be in the form of a secondary particle in which a plurality of primary particles are aggregated, and the aluminum content in the primary particle may be the same or similar regardless of the position of the primary particle. That is, if a primary particle is selected at an arbitrary position in the cross section of the secondary particle and the aluminum content in the inside of the primary particle, not at the interface, is measured, the aluminum content may be expressed as the same / similar / uniform regardless of the position of the primary particle, that is, whether the primary particle is close to the center or the surface of the secondary particle. In such a structure, a stable layered structure can be maintained even in the absence or presence of only a small amount of cobalt, and no aluminum by-products or aluminum agglomerates are generated, so that the capacity, efficiency, and life characteristics of the positive electrode active material can be improved simultaneously.
[0027] The lithium nickel-manganese composite oxide can be specifically represented by the following chemical formula 1. [Chemical formula 1] Li a1 Ni x1 Mn y1 Al z1 M 1 w1 O 2-b1 X b1
[0028] In the chemical formula 1, 0.9≦a1≦1.8, 0.6≦x1≦0.8, 0.1≦y1≦0.4, 0≦z1≦0.03, 0≦w1≦0.3, 0.9≦x1+y1+z1+w1≦1.1, and 0≦b1≦0.1; M 1is one or more elements selected from B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W, Y, and Zr, and X is one or more elements selected from F, P, and S.
[0029] In Chemical Formula 1, 0.9 ≤ a1 ≤ 1.5, or 0.9 ≤ a1 ≤ 1.2 may hold. Further, Chemical Formula 1 may contain aluminum, and in this case, 0.6 ≤ x1 ≤ 0.8, 0.1 ≤ y1 ≤ 0.39, 0.01 ≤ z1 ≤ 0.03, and 0 ≤ w1 ≤ 0.29 can be satisfied. For example, 0.6 ≤ x1 ≤ 0.8, 0.1 ≤ y1 ≤ 0.39, 0.01 < z1 ≤ 0.03, and 0 ≤ w1 ≤ 0.29 can be satisfied.
[0030] In Chemical Formula 1, for example, 0.6 ≤ x1 ≤ 0.79, 0.6 ≤ x1 ≤ 0.78, 0.6 ≤ x1 ≤ 0.75, 0.65 ≤ x1 ≤ 0.8, or 0.7 ≤ x1 ≤ 0.79 may hold, 0.1 ≤ y1 ≤ 0.35, 0.1 ≤ y1 ≤ 0.30, 0.1 ≤ y1 ≤ 0.29, 0.15 ≤ y1 ≤ 0.39, or 0.2 ≤ y1 ≤ 0.3 may hold, 0.01 ≤ z1 ≤ 0.025, 0.01 < z1 ≤ 0.02, or 0.01 < z1 ≤ 0.019 may hold, and 0 ≤ w1 ≤ 0.28, 0 ≤ w1 ≤ 0.27, 0 ≤ w1 ≤ 0.26, 0 ≤ w1 ≤ 0.25, 0 ≤ w1 ≤ 0.24, 0 ≤ w1 ≤ 0.23, 0 ≤ w1 ≤ 0.22, 0 ≤ w1 ≤ 0.21, 0 ≤ w1 ≤ 0.2, 0 ≤ w1 ≤ 0.15, 0 ≤ w1 ≤ 0.1, or 0 ≤ w1 ≤ 0.09, etc., may hold.
[0031] The lithium nickel - manganese - based composite oxide may be a cobalt - free compound that does not contain cobalt or contains a very small amount of cobalt. For example, in the lithium nickel - manganese - based composite oxide, the content of cobalt with respect to 100 mol% of the total metal excluding lithium may be 0 mol% to 0.01 mol%.
[0032] The core particles may be in the form of secondary particles formed by agglomeration of multiple primary particles. The secondary particles may be spherical, ellipsoidal, polyhedral, or irregular in shape, while the primary particles may be spherical, ellipsoidal, plate-like, or a combination thereof.
[0033] The core particles are susceptible to chemical attack by components in the electrolyte when the battery is used under high voltage or high temperature conditions, and therefore side reactions with the electrolyte may occur frequently, resulting in a large amount of gas generation, which may reduce the battery life and safety. However, such problems can be solved by introducing a coating layer according to one embodiment described below.
[0034] First Coating Layer The Al content in the first coating layer may be 0.1 mol% to 2 mol% based on 100 mol% of all metals excluding lithium in the positive electrode active material, for example, 0.2 mol% to 1.9 mol%, 0.3 mol% to 1.8 mol%, 0.5 mol% to 1.5 mol%, or 0.8 mol% to 1.3 mol%. This means only the content of aluminum contained in the first coating layer, separate from the aluminum contained in the core particles. The aluminum content in the first coating layer may be measured, for example, through SEM-EDS analysis of the surface or cross section of the positive electrode active material. When the aluminum content in the first coating layer satisfies the above range, it is possible to form a coating layer with a thin and uniform thickness, the resistance of the positive electrode active material does not increase, and side reactions with the electrolyte are effectively suppressed, thereby improving the life characteristics of the lithium secondary battery under high voltage and high temperature conditions. For example, if the aluminum content of the first coating layer is too high, a uniform coating layer may not be formed or the resistance may increase, resulting in reduced charge / discharge efficiency and reduced life characteristics. Conversely, if the aluminum content of the first coating layer is too low, a coating layer of appropriate thickness may not be formed, resulting in reduced effectiveness in suppressing side reactions with the electrolyte.
[0035] The first coating layer may be in the form of a film that continuously surrounds the surface of the core particle, for example, in the form of a shell that surrounds the entire surface of the core particle. This is different from a structure in which only a part of the surface of the core particle is partially coated. According to one embodiment, the first coating layer may be formed to a very thin and uniform thickness while being formed in a form that entirely surrounds the surface of the core particle, so that the positive electrode active material has improved structural stability without increasing resistance or decreasing capacity, side reactions with the electrolyte may be effectively suppressed, and the amount of gas generation under high voltage and high temperature conditions may be reduced, thereby realizing long life characteristics.
[0036] The thickness of the first coating layer may be 5 nm to 40 nm, for example, 5 nm to 30 nm, or 5 nm to 20 nm. When the first coating layer satisfies the above thickness range, the coating can improve the structural stability of the positive electrode active material without increasing the resistance or decreasing the capacity, and can effectively suppress side reactions with the electrolyte. The thickness of the coating layer can be measured, for example, by SEM, TEM, TOF-SIMS, XPS, or EDS analysis, and the thickness range of the coating layer can be measured by TEM-EDS line profile.
[0037] The first coating layer may be thicker than the second coating layer described below.
[0038] The first coating layer is characterized by being thin, at a thickness of several tens to several hundreds of nanometers, but uniform in thickness. For example, the deviation of the thickness of the first coating layer within one positive electrode active material particle may be 20% or less, 18% or less, or 15% or less. Here, the deviation of the thickness of the coating layer refers to the thickness of the coating layer within one positive electrode active material particle. The deviation of the thickness of the coating layer may be, for example, a value obtained by measuring the thickness at 10 or more points in an electron microscope image of a cross section of one positive electrode active material particle, calculating the arithmetic average, dividing the absolute value of the difference between one data and the arithmetic average value by the arithmetic average value, and multiplying the result by 100. The deviation or standard deviation of the thickness of the first coating layer satisfies the above range, which means that a coating layer of uniform thickness is well formed in the form of a film on the surface of the positive electrode active material particle, thereby improving the structural stability of the positive electrode active material, effectively suppressing side reactions with the electrolyte, and minimizing the increase in resistance and the decrease in capacity due to the coating.
[0039] The first coating layer can include, for example, aluminum oxide, lithium-aluminum oxide, or a combination thereof. The first coating layer can have a layered structure. That is, the compound included in the first coating layer can have a layered structure.
[0040] In addition to aluminum, the first coating layer may further contain nickel, manganese, or a combination thereof.
[0041] Second Coating Layer The Mn content in the second coating layer may be 0.01 mol% to 1 mol% based on 100 mol% of all metals excluding lithium in the positive electrode active material, for example, 0.01 mol% to 0.9 mol%, 0.01 mol% to 0.7 mol%, 0.05 mol% to 0.5 mol%, or 0.1 mol% to 0.4 mol%. The Mn content in the second coating layer may be measured, for example, through SEM-EDS analysis of the surface or cross section of the positive electrode active material. When the Mn content in the second coating layer satisfies the above range, a thin and uniform coating layer can be formed, the resistance of the positive electrode active material does not increase, and side reactions with the electrolyte are effectively suppressed, thereby improving the life characteristics of the lithium secondary battery under high voltage and high temperature conditions. For example, if the Mn content of the second coating layer is too high, a uniform coating layer may not be formed or the resistance may increase, resulting in reduced charge / discharge efficiency and life characteristics. Conversely, if the Mn content of the second coating layer is too low, a coating layer of appropriate thickness may not be formed, the effect of suppressing side reactions with the electrolyte may decrease, and the charge / discharge efficiency and high-temperature life characteristics may decrease.
[0042] The second coating layer may be in the form of a film or shell that continuously surrounds the surface of the first coating layer. According to one embodiment, the second coating layer may be formed to a very thin and uniform thickness while being formed to completely surround the outermost surface of the positive electrode active material, so that the positive electrode active material has improved structural stability without an increase in resistance or a decrease in capacity, and side reactions with the electrolyte may be effectively suppressed, and the amount of gas generation under high voltage and high temperature conditions may be reduced, thereby realizing long life characteristics.
[0043] The thickness of the second coating layer may be 10 nm or less, for example, 0.1 nm to 10 nm, 0.5 nm to 9 nm, 1 nm to 7 nm, or 1 nm to 5 nm. When the second coating layer satisfies the above thickness range, the coating can improve the structural stability of the positive electrode active material without increasing the resistance or decreasing the capacity, and can effectively suppress side reactions with the electrolyte. The thickness of the coating layer can be measured, for example, through SEM, TEM, TOF-SIMS, XPS, or EDS analysis, and the thickness range of the coating layer can be measured through a TEM-EDS line profile.
[0044] The second coating layer is characterized by being thin at a thickness of a few nanometers, but uniform in thickness. For example, the deviation of the thickness of the second coating layer within one positive electrode active material particle may be 20% or less, 18% or less, or 15% or less. Here, the deviation of the thickness of the coating layer refers to the thickness of the coating layer within one positive electrode active material particle. The deviation of the thickness of the coating layer may be, for example, a value obtained by measuring the thickness at 10 or more points in an electron microscope image of a cross section of one positive electrode active material particle, calculating the arithmetic average, dividing the absolute value of the difference between one data and the arithmetic average value by the arithmetic average value, and multiplying the result by 100. The deviation or standard deviation of the thickness of the second coating layer satisfies the above range, which means that a coating layer of uniform thickness is well formed in the form of a film on the outermost surface of the positive electrode active material particle, thereby improving the structural stability of the positive electrode active material, effectively suppressing side reactions with the electrolyte, and minimizing the increase in resistance and the decrease in capacity due to the coating.
[0045] The second coating layer may further include Al in addition to Mn. The second coating layer may include, for example, manganese oxide, lithium-manganese oxide, aluminum-manganese oxide, lithium-aluminum-manganese oxide, or a combination thereof. The second coating layer may have a layered structure, and may optionally further include a spinel structure.
[0046] Meanwhile, the first coating layer may be thicker than the second coating layer. For example, the ratio of the thickness of the second coating layer to the thickness of the first coating layer may be less than 0.5, for example, 0.4 or less, or 0.3 or less. When the thicknesses of the first coating layer and the second coating layer satisfy such a relationship, the coating can improve the structural stability of the positive electrode active material without increasing the resistance or decreasing the capacity, and can effectively suppress side reactions with the electrolyte to improve high voltage characteristics and high temperature characteristics.
[0047] The Al content of the first coating layer may be greater than the Mn content of the second coating layer. Here, the content may refer to the molar content, and may refer to the molar content relative to 100 mol% of metals excluding lithium in the positive electrode active material. For example, the ratio of the Mn content of the second coating layer to the Al content of the first coating layer may be less than 0.5, for example, 0.4 or less, 0.3 or less. When the Al content of the first coating layer and the Mn content of the second coating layer satisfy such a relationship, the structural stability of the positive electrode active material can be improved without increasing resistance or decreasing capacity due to the coating, and side reactions with the electrolyte can be effectively suppressed to improve high voltage characteristics and high temperature characteristics.
[0048] Grain boundary coating part Meanwhile, aluminum may be diffused into the core particles during the formation of the first coating layer. Thus, the positive electrode active material according to an embodiment may further include a grain boundary coating portion containing aluminum and located on the surface of the primary particle inside the secondary particle. Here, the secondary particle refers to the core particle, and the inside of the secondary particle may refer to the entire inside of the secondary particle except for the surface, or may refer to a region from the surface of the secondary particle to about 60% of the radius in the direction toward the center of the secondary particle. The grain boundary coating portion is a concept that is different from the coating layer on the surface of the core particle, and refers to a coating portion formed on the surface of the primary particle located inside the core particle. The presence of the grain boundary coating portion may be confirmed by SEM-EDS analysis of a cross section of the positive electrode active material. The formation of the aluminum grain boundary coating portion may further stabilize the structure of the positive electrode active material, and improve the life characteristics.
[0049] The aluminum content in the grain boundary coating portion is not particularly limited, and as an example, the aluminum content in the grain boundary coating portion may be less than the aluminum content in the coating layer.
[0050] In addition to aluminum, the grain boundary coating may further include nickel, manganese, yttrium, or a combination thereof.
[0051] The average particle size (D 50 The average particle size is determined by measuring the size (diameter or major axis length) of 20 or more particles randomly from a scanning electron microscope image of the positive electrode active material to obtain a particle size distribution, and calculating the diameter (D) of the particle having a cumulative volume of 50% by volume from the particle size distribution. 50 When the average particle size of the positive electrode active material satisfies the above range, high capacity and long life can be achieved, which may be advantageous in forming the coating layer according to an embodiment.
[0052] In the positive electrode active material according to an embodiment, the content of cobalt may be, for example, 0.01 mol % or less, 0.005 mol % or less, 0.001 mol % or less, for example, 0 mol % to 0.01 mol %, based on 100 mol % of all metals excluding lithium. The positive electrode active material according to an embodiment may be, for example, a cobalt-free positive electrode active material.
[0053] In addition, the positive electrode active material according to an embodiment may be characterized as being sodium-free. Although sodium ions are generally used in the manufacturing process of a positive electrode active material, according to the manufacturing method described below, it is possible to form core particles with a stable structure and a coating layer with a uniform thickness without using sodium ions.
[0054] Method for producing positive electrode active material In one embodiment, a method for producing a positive electrode active material is provided, comprising: mixing a layered nickel-manganese composite hydroxide and a lithium source, performing a first heat treatment to obtain a lithium nickel-manganese composite oxide, adding an Al source to an aqueous solvent, adding and mixing the lithium nickel-manganese composite oxide, adding and mixing a Mn source, drying the mixture, and performing a second heat treatment. The positive electrode active material described above can be produced through the method.
[0055] The layered nickel-manganese composite hydroxide is a precursor of a core particle, and may be in the form of a secondary particle formed by agglomeration of a plurality of primary particles, and may contain no or a very small amount of cobalt, for example, a cobalt-free nickel-manganese composite hydroxide. The nickel-manganese-aluminum composite hydroxide may be prepared by a general coprecipitation method.
[0056] In the layered nickel-manganese composite hydroxide, the nickel content may be 60 mol% or more relative to 100 mol% of the total metal, for example, 60 mol% to 80 mol%, 65 mol% to 80 mol%, 70 mol% to 80 mol%, 60 mol% to 79 mol%, 60 mol% to 78 mol%, or 60 mol% to 75 mol%, etc. When the nickel content satisfies the above range, a high capacity can be achieved, and structural safety can be improved even if the cobalt content is reduced.
[0057] The manganese content in the layered nickel-manganese composite hydroxide may be 10 mol% or more relative to 100 mol% of the total metal, for example, 10 mol% to 40 mol%, 15 mol% to 39 mol%, 15 mol% to 35 mol%, 15 mol% to 30 mol%, 20 mol% to 30%, etc.
[0058] In addition, when the layered nickel-manganese composite hydroxide further contains aluminum, the aluminum content may be 0.1 mol% or more, 0.5 mol% or more, or 1 mol% or more, for example, 1 mol% to 3 mol%, 1 mol% to 2.5 mol%, 1 mol% to 2 mol%, or 1 mol% to 1.9 mol%, based on 100 mol% of the total metal. When the manganese and aluminum contents in the composite hydroxide satisfy the above ranges, the structural safety of the positive electrode active material can be improved while realizing a high capacity, and the production cost can be reduced to improve the economic efficiency.
[0059] According to an embodiment, a method for producing a positive electrode active material may use a nickel-manganese-aluminum composite hydroxide as a precursor, in which aluminum is uniformly dispersed within the structure, by using an aluminum raw material in the preparation of a precursor without additionally doping aluminum in the preparation of core particles. When using such a precursor, a positive electrode active material in which a layered structure is stably maintained even after repeated charging and discharging without the need for cobalt can be produced, and since aluminum by-products or aluminum aggregates are not formed, the capacity, efficiency and life characteristics of the positive electrode active material can be improved.
[0060] In the layered nickel-manganese composite hydroxide, the cobalt content may be 0.01 mol% or less, 0.005 mol% or less, or 0.001 mol% or less, based on 100 mol% of the total metal. Such nickel-manganese composite hydroxide is economical because it can avoid the increase in unit price due to cobalt, and it can be said to have maximized capacity and improved structural stability.
[0061] The layered nickel-manganese composite hydroxide can be represented, for example, by the following chemical formula 2. [Chemical formula 2] Ni x2 Mn y2 Al z2 M 2 w2 (OH)2
[0062] In chemical formula 2, 0.6≦x2≦0.8, 0.1≦y2≦0.40≦z2≦0.03, 0≦w2≦0.3, and 0.9≦x2+y2+z2+w2≦1.1; M 2 is one or more elements selected from B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W, Y, and Zr.
[0063] In Formula 2, for example, 6≦x2≦0.8, 0.1≦y2≦0.39, 0.01≦z2≦0.03, and 0≦w2≦0.29.
[0064] The layered nickel-manganese composite hydroxide is in the form of particles, and the average particle size (D 50 ) may be 1 μm to 25 μm, 5 μm to 20 μm, 10 μm to 20 μm, 11 μm to 18 μm, or 12 μm to 15 μm.
[0065] The layered nickel-manganese composite hydroxide and the lithium raw material may be mixed in a molar ratio of 1:0.9 to 1:1.8, for example, 1:0.9 to 1:1.5 or 1:0.9 to 1:1.2. The first heat treatment may be performed in an oxygen atmosphere, for example, at a temperature range of 750°C to 950°C, or 780°C to 900°C, or 810°C to 890°C, for 2 hours to 20 hours, or 4 hours to 12 hours. A lithium nickel-manganese composite oxide can be obtained through the heat treatment. The obtained composite oxide is substantially the same as the description of the core particles in the positive electrode active material portion.
[0066] The layered lithium nickel-manganese composite oxide has a significantly different content of residual lithium on the particle surface from existing nickel-based oxides of other compositions, such as lithium nickel-cobalt-manganese composite oxide and lithium nickel-cobalt-aluminum composite oxide, and has many different surface properties, making it impossible to form a good coating layer with a uniform film shape using existing coating methods. In one embodiment, a method is proposed that can improve high voltage characteristics by forming a uniform coating layer with a very thin thickness on the surface of a lithium nickel-manganese composite oxide with a very small cobalt content and a nickel content of 60 mol% or more.
[0067] In one embodiment, an Al raw material is added to an aqueous solvent and mixed, and then a layered lithium nickel-manganese composite oxide is added and mixed to induce a first coating layer on the surface of a layered lithium nickel-manganese composite oxide particle (core particle). Next, a Mn raw material is added to the mixed solution and mixed to induce a second coating layer. Then, the solvent is removed from the mixed solution, and the solution is dried, and a second heat treatment is performed to obtain a positive electrode active material in which an Al-containing first coating layer and a Mn-containing second coating layer are sequentially formed on the surface of the core particle. This can be said to be a continuous wet coating method.
[0068] The aqueous solvent may include distilled water, an alcohol-based solvent, or a combination thereof. The Al raw material may include, for example, aluminum nitrate, aluminum sulfate, aluminum carbonate, aluminum hydroxide, or a combination thereof. As an example, the Al raw material may include aluminum sulfate, which is advantageous in forming a first coating layer having a uniform thickness on the surface of the lithium nickel-manganese composite oxide particles.
[0069] The Al raw material is a raw material for forming the coating layer, and the Al content in the Al raw material may be designed to be 0.1 mol% to 2 mol% with respect to 100 mol% of the total metals excluding lithium in the finally obtained positive electrode active material, for example, 0.2 mol% to 1.9 mol%, 0.3 mol% to 1.8 mol%, 0.5 mol% to 1.5 mol%, or 0.8 mol% to 1.3 mol%. By designing the Al coating content within the above range, a first coating layer having a thin and uniform thickness of tens to hundreds of nanometers can be formed, and the amount of gas generation of the lithium secondary battery under high voltage or high temperature usage conditions can be reduced, and high capacity and long life characteristics can be improved.
[0070] The solution in which the Al raw material is added to the aqueous solvent may have a pH of 1.5 to 3.5, for example, 2.0 to 3.4, 2.5 to 3.3, 2.7 to 3.3, or 2.9 to 3.2. The lithium nickel-manganese composite oxide may be added to the aqueous solvent in which the aluminum raw material is mixed and mixed for about 5 to 80 minutes, or 5 to 60 minutes, or 5 to 40 minutes. The pH of the mixed solution after stirring may be 4.5 to 8.5, for example, 5.0 to 8.0, 5.5 to 7.5, or 6.0 to 7.0. When such conditions are satisfied, it is advantageous for a first coating layer of uniform thickness to be formed.
[0071] The Mn raw material may include, for example, manganese nitrate, manganese sulfate, manganese carbonate, manganese hydroxide, or a combination thereof. The Mn content in the Mn raw material may be designed to be 0.01 mol% to 1 mol% with respect to 100 mol% of the total metals excluding lithium in the positive electrode active material, for example, 0.01 mol% to 0.9 mol%, 0.01 mol% to 0.7 mol%, 0.05 mol% to 0.5 mol%, or 0.1 mol% to 0.4 mol%. By designing the Mn coating content within the above range, a second coating layer having a thin thickness of several nanometers and a uniform thickness can be formed, and the performance of the lithium secondary battery under high voltage or high temperature use conditions can be improved, and high capacity and long life characteristics can be improved.
[0072] The Mn raw material may be added and mixed for about 5 to 80 minutes, or 5 to 60 minutes, or 10 to 40 minutes. The pH of the final mixed solution after stirring may be 4.5 to 8.5, for example, 5.0 to 8.0, 5.5 to 7.5, or 6.0 to 7.0. When such conditions are satisfied, it is advantageous for a second coating layer of uniform thickness to be formed.
[0073] The solvent can be removed from the mixed solution and then dried, for example, at 40°C to 240°C, 100°C to 220°C, or 150°C to 200°C.
[0074] The second heat treatment can be carried out, for example, in an oxygen atmosphere at a temperature range of 700°C to 850°C, 750°C to 840°C, or 800°C to 830°C for 2 hours to 20 hours, or 3 hours to 10 hours. The second heat treatment temperature may be lower than the first heat treatment temperature, and the second heat treatment time may be the same as or shorter than the first heat treatment time. By carrying out the second heat treatment under such conditions, a desired coating layer can be obtained.
[0075] positive electrode In one embodiment, the positive electrode includes a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector, the positive electrode active material layer including the positive electrode active material described above. The positive electrode active material layer may further include other types of positive electrode active materials in addition to the positive electrode active materials described above. The positive electrode active material layer may also optionally include a binder, a conductive agent, or a combination thereof.
[0076] According to one embodiment, the loading level of the positive electrode active material layer is 10 mg / cm 2 ~40mg / cm 2 For example, 10 mg / cm 2 ~30mg / cm 2 or 10 mg / cm 2 ~20mg / cm 2 In addition, the density of the positive electrode active material layer in the final rolled positive electrode may be 3.3 g / cc to 3.7 g / cc, for example, 3.3 g / cc to 3.6 g / cc or 3.4 g / cc to 3.58 g / cc. When applying the positive electrode active material according to an embodiment, it is advantageous to achieve such a loading level and positive electrode density, and a positive electrode satisfying the loading level and positive electrode density in the above ranges is suitable for realizing a lithium secondary battery with a high capacity and high energy density.
[0077] binder The binder serves to adhere the positive electrode active material particles to each other well and to adhere the positive electrode active material to the current collector well. Representative examples of the binder include, but are not limited to, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, epoxy resin, (meth)acrylic resin, polyester resin, nylon, etc.
[0078] Conductive Agent The conductive agent is used to impart electrical conductivity to the electrode, and any electronically conductive material that does not undergo chemical changes in the battery that is constructed can be used. Examples of the conductive agent include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, carbon fiber, carbon nanofiber, and carbon nanotube; metal-based materials containing copper, nickel, aluminum, silver, and the like in the form of metal powder or metal fiber; conductive polymers such as polyphenylene derivatives; and mixtures thereof.
[0079] The content of the binder and the conductive agent may be 0.5% by weight to 5% by weight, respectively, relative to 100% by weight of the positive electrode active material layer.
[0080] The positive electrode current collector can be made of Al, but is not limited to this.
[0081] negative electrode The negative electrode can include a current collector and a negative electrode active material layer located on the current collector, the negative electrode active material layer including a negative electrode active material and can further include a binder, a conductive agent, or a combination thereof.
[0082] negative electrode active material The negative electrode active material includes a material capable of reversibly inserting / extracting lithium ions, lithium metal, a lithium metal alloy, a material capable of being doped and dedoped with lithium, or a transition metal oxide.
[0083] The material capable of reversibly inserting / extracting lithium ions may be a carbon-based negative electrode active material, and may include, for example, crystalline carbon, amorphous carbon, or a combination thereof. Examples of the crystalline carbon include graphite such as amorphous, plate-like, flake-like, spherical, or fibrous natural graphite or artificial graphite, and examples of the amorphous carbon include soft carbon, hard carbon, mesophase pitch carbide, and calcined coke.
[0084] As the alloy of the lithium metal, an alloy of lithium and a metal selected from Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and Sn can be used.
[0085] As the substance capable of doping and undoping the lithium, an Si-based negative electrode active material or an Sn-based negative electrode active material can be used. As the Si-based negative electrode active material, silicon, a silicon-carbon composite, SiOx (0 < x < 2), an Si-Q alloy (where Q is an element selected from an alkali metal, an alkaline earth metal, a Group 13 element, a Group 14 element (excluding Si), a Group 15 element, a Group 16 element, a transition metal, a rare earth element, and combinations thereof, for example, Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Tl, Ge, P, As, Sb, Bi, S, Se, Te, Po, and combinations thereof), or a combination thereof can be used. As the Sn-based negative electrode active material, Sn, SnO2, an Sn alloy, or a combination thereof can be used.
[0086] The silicon-carbon composite can be a composite of silicon and amorphous carbon. The average particle size (D 50 ) of the silicon-carbon composite particles can be, for example, 0.5 μm to 20 μm. According to one embodiment, the silicon-carbon composite can be in a form in which silicon particles and amorphous carbon are coated on the surface of the silicon particles. For example, it can include secondary particles (cores) formed by granulating primary silicon particles and an amorphous carbon coating layer (shell) located on the surface of the secondary particles. The amorphous carbon is also located between the primary silicon particles, and for example, the primary silicon particles can be coated with amorphous carbon. The secondary particles can be dispersed and present in an amorphous carbon matrix.
[0087] The silicon-carbon composite may further contain crystalline carbon. For example, the silicon-carbon composite may include a core containing crystalline carbon and silicon particles, and an amorphous carbon coating layer located on the surface of the core. The crystalline carbon may be artificial graphite, natural graphite, or a combination thereof. Examples of the amorphous carbon include soft carbon, hard carbon, mesophase pitch carbide, and calcined coke.
[0088] When the silicon-carbon composite contains silicon and amorphous carbon, the content of silicon may be 10% to 50% by weight based on 100% by weight of the silicon-carbon composite, and the content of amorphous carbon may be 50% to 90% by weight. When the composite contains silicon, amorphous carbon, and crystalline carbon, the content of silicon may be 10% to 50% by weight based on 100% by weight of the silicon-carbon composite, the content of crystalline carbon may be 10% to 70% by weight, and the content of amorphous carbon may be 20% to 40% by weight.
[0089] Also, the thickness of the amorphous carbon coating layer may be 5 nm to 100 nm. The average particle diameter (D 50 ) of the silicon particles (primary particles) may be 10 nm to 1 μm, or 10 nm to 200 nm. The silicon particles may exist alone as silicon, in the form of a silicon alloy, or in an oxidized form. The oxidized form of silicon may be represented by SiO x (0 < x < 2). At this time, the atomic content ratio of Si:O indicating the degree of oxidation may be 99:1 to 33:67. In this specification, unless otherwise defined, the average particle diameter (D 50 ) means the diameter of the particle with a cumulative volume of 50% by volume in the particle size distribution.
[0090] The Si-based negative electrode active material or the Sn-based negative electrode active material can be used by mixing with a carbon-based negative electrode active material. When the Si-based negative electrode active material or the Sn-based negative electrode active material is mixed with the carbon-based negative electrode active material, the mixing ratio may be 1:99 to 90:10 by weight.
[0091] binder The binder serves to effectively adhere the negative active material particles to each other and to the current collector. The binder may be a non-aqueous binder, an aqueous binder, a dry binder, or a combination thereof.
[0092] Non-aqueous binders include polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene propylene copolymers, polystyrene, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamideimide, polyimide, or combinations thereof.
[0093] The water-based binder may be selected from styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, (meth)acrylonitrile-butadiene rubber, (meth)acrylic rubber, butyl rubber, fluororubber, polyethylene oxide, polyvinylpyrrolidone, polyepichlorohydrin, polyphosphazene, poly(meth)acrylonitrile, ethylene propylene diene copolymer, polyvinylpyridine, chlorosulfonated polyethylene, latex, polyester resin, (meth)acrylic resin, phenolic resin, epoxy resin, polyvinyl alcohol, and combinations thereof.
[0094] When an aqueous binder is used as the negative electrode binder, a cellulose-based compound capable of imparting viscosity may be further included. As the cellulose-based compound, one or more of carboxymethylcellulose, hydroxypropylmethylcellulose, methylcellulose, or alkali metal salts thereof may be mixed and used. As the alkali metal, Na, K, or Li may be used.
[0095] The dry binder is a polymeric material capable of being fiberized, and can be, for example, polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyethylene oxide, or combinations thereof.
[0096] Conductive Agent The conductive agent is used to impart electrical conductivity to the electrode, and any electronically conductive material that does not undergo chemical changes in the battery that is constructed can be used. Specific examples include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, carbon fiber, carbon nanofiber, and carbon nanotube; metal-based materials in the form of metal powder or metal fiber, including copper, nickel, aluminum, and silver; conductive polymers such as polyphenylene derivatives; and mixtures thereof.
[0097] The content of the negative electrode active material may be 95% to 99.5% by weight relative to 100% by weight of the negative electrode active material layer, and the content of the binder may be 0.5% to 5% by weight relative to 100% by weight of the negative electrode active material layer. For example, the negative electrode active material layer may contain 90% to 99% by weight of the negative electrode active material, 0.5% to 5% by weight of the binder, and 0.5% to 5% by weight of the conductive agent.
[0098] Current collector The negative electrode current collector can include, for example, indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), lithium (Li), or alloys thereof, and can be in the form of a foil, sheet, or foam. The thickness of the negative electrode current collector can be, for example, 1 μm to 20 μm, 5 μm to 15 μm, or 7 μm to 10 μm.
[0099] electrolyte The electrolyte for a lithium secondary battery can be, by way of example, an electrolytic solution, which can include a non-aqueous organic solvent and a lithium salt.
[0100] The non-aqueous organic solvent serves as a medium through which the ions involved in the electrochemical reactions of the battery can migrate. The non-aqueous organic solvent may be a carbonate-, ester-, ether-, ketone-, or alcohol-based solvent, an aprotic solvent, or a combination thereof.
[0101] Examples of the carbonate solvent include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), etc. Examples of the ester solvent include methyl acetate, ethyl acetate, n-propyl acetate, dimethyl acetate, methyl propionate, ethyl propionate, decanolide, mevalonolactone, valerolactone, caprolactone, etc. Examples of the ether solvent include dibutyl ether, tetraglyme, diglyme, dimethoxyethane, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, and tetrahydrofuran. Examples of the ketone solvent include cyclohexanone. Examples of the alcohol solvent include ethyl alcohol and isopropyl alcohol. Examples of the aprotic solvent include nitriles such as R-CN (R is a straight-chain, branched, or cyclic hydrocarbon group having 2 to 20 carbon atoms, and may contain a double bond, an aromatic ring, or an ether group); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolane and 1,4-dioxolane; and sulfolanes.
[0102] The non-aqueous organic solvent may be used alone or in combination of two or more kinds. When two or more kinds are used in combination, the mixing ratio may be appropriately adjusted depending on the desired battery performance, which is widely understood by those working in the field.
[0103] When a carbonate-based solvent is used, a cyclic carbonate and a chain carbonate may be mixed and used, and the cyclic carbonate and the chain carbonate may be mixed in a volume ratio of 1:1 to 1:9.
[0104] The non-aqueous organic solvent may further include an aromatic hydrocarbon organic solvent. For example, a carbonate solvent and an aromatic hydrocarbon organic solvent may be mixed in a volume ratio of 1:1 to 30:1.
[0105] The electrolyte may further contain a vinyl ethyl carbonate, vinylene carbonate or ethylene carbonate based compound to improve the battery life.
[0106] Representative examples of the ethylene carbonate-based compounds include fluoroethylene carbonate, difluoroethylene carbonate, chloroethylene carbonate, dichloroethylene carbonate, bromoethylene carbonate, dibromoethylene carbonate, nitroethylene carbonate, and cyanoethylene carbonate.
[0107] Lithium salts are substances dissolved in organic solvents and act as a source of lithium ions in the battery to enable basic lithium secondary battery operation and to facilitate the movement of lithium ions between the positive and negative electrodes. Representative examples of lithium salts include LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiAlO2, LiAlCl4, LiPO2F2, LiCl, LiI, LiN(SO3C2F5)2, Li(FSO2)2N (lithium bis(fluorosulfonyl)imide; LiFSI), LiC4F9SO3, LiN(C x F 2x+1 SO2)(C y F 2y+1SO2) (x and y are integers from 1 to 20), lithium trifluoromethanesulfonate, lithium tetrafluoroethanesulfonate, lithium difluorobis(oxalato)phosphate (LiDFOB), and lithium bis(oxalato)borate (LiBOB).
[0108] The lithium salt is preferably used at a concentration within the range of 0.1 M to 2.0 M. When the lithium salt concentration is within this range, the electrolyte has appropriate ion conductivity and viscosity, and therefore can exhibit excellent performance and allow lithium ions to migrate effectively.
[0109] Lithium secondary battery In one embodiment, a lithium secondary battery is provided that includes the above-described positive electrode, negative electrode, and electrolyte. For example, the lithium secondary battery may include a positive electrode, a negative electrode, a separator disposed between the positive electrode and the negative electrode, and an electrolyte.
[0110] Lithium secondary batteries can be classified into cylindrical, square, pouch, coin, and other types according to their shapes. FIGS. 1 to 4 are schematic diagrams showing a lithium secondary battery according to an embodiment, in which FIG. 1 shows a circular type, FIG. 2 shows a square type, and FIGS. 3 and 4 show a pouch type battery. Referring to FIGS. 1 to 4, a lithium secondary battery 100 may include an electrode assembly 40 having a separator 30 between a positive electrode 10 and a negative electrode 20, and a case 50 in which the electrode assembly 40 is housed. The positive electrode 10, the negative electrode 20, and the separator 30 may be impregnated with an electrolyte (not shown). The lithium secondary battery 100 may include a sealing member 60 that seals the case 50 as shown in FIG. 1. Also, the lithium secondary battery 100 in FIG. 2 may include a positive electrode lead tab 11, a positive electrode terminal 12, a negative electrode lead tab 21, and a negative electrode terminal 22. As shown in FIGS. 3 and 4, the lithium secondary battery 100 may include electrode tabs 70, i.e., a positive electrode tab 71 and a negative electrode tab 72, which serve as electrical paths for conducting the current generated in the electrode assembly 40 to the outside.
[0111] The lithium secondary battery according to an embodiment may be capable of being charged at a high voltage or may be suitable for use at a high voltage. For example, the charging voltage of the lithium secondary battery may be 4.45 V or more, such as 4.45 V to 4.7 V, 4.45 V to 4.6 V, or 4.45 V to 4.55 V. By applying the positive electrode active material according to an embodiment, the lithium secondary battery can significantly reduce the amount of gas generated even when charged at a high voltage, and can achieve high capacity and long life characteristics.
[0112] Separator Depending on the type of lithium secondary battery, a separator may be present between the positive electrode and the negative electrode. As such a separator, polyethylene, polypropylene, polyvinylidene fluoride, or a multi-layer film of two or more layers of these may be used, and it is of course possible to use a mixed multi-layer film such as a polyethylene / polypropylene two-layer separator, a polyethylene / polypropylene / polyethylene three-layer separator, or a polypropylene / polyethylene / polypropylene three-layer separator.
[0113] The separator may include a porous substrate and a coating layer comprising an organic material, an inorganic material, or a combination thereof located on one or both sides of the porous substrate.
[0114] The porous substrate may be a polymer membrane formed of any one polymer selected from polyolefins such as polyethylene and polypropylene, polyesters such as polyethylene terephthalate and polybutylene terephthalate, polyacetal, polyamide, polyimide, polycarbonate, polyether ketone, polyaryl ether ketone, polyetherimide, polyamide imide, polybenzimidazole, polyether sulfone, polyphenylene oxide, cyclic olefin copolymer, polyphenylene sulfide, polyethylene naphthalate, glass fiber, Teflon (registered trademark), and polytetrafluoroethylene, or a copolymer or mixture of two or more of these polymers.
[0115] The porous substrate can have a thickness of about 1 μm to 40 μm, for example, 1 μm to 30 μm, 1 μm to 20 μm, 5 μm to 15 μm, or 10 μm to 15 μm.
[0116] The organic material may include a (meth)acrylic copolymer including a first structural unit derived from a (meth)acrylamide, and a second structural unit including at least one of a structural unit derived from (meth)acrylic acid or a (meth)acrylate, and a structural unit derived from (meth)acrylamidosulfonic acid or a salt thereof.
[0117] The inorganic substances are Al2O3, SiO2, TiO2, SnO2, CeO2, MgO, NiO, CaO, GaO, ZnO, ZrO2, Y2O3, SrTiO3, BaTiO3, Mg(OH) 2、 The inorganic particles may include, but are not limited to, inorganic particles selected from boehmite and combinations thereof. The average particle size (D 50 ) may be 1 nm to 2000 nm, for example, 100 nm to 1000 nm, or 100 nm to 700 nm.
[0118] The organic material and the inorganic material may be mixed in one coating layer, or may be stacked in a coating layer including an organic material and a coating layer including an inorganic material.
[0119] The thickness of each of the coating layers may be from 0.5 μm to 20 μm, for example, from 1 μm to 10 μm, or from 1 μm to 5 μm.
[0120] Examples of the present invention and comparative examples are described below. The following examples are merely illustrative of the present invention, and the present invention is not limited to the following examples.
[0121] Example 1 1. Manufacturing of positive electrode active material Ni 0.75 Mn0.23 Al 0.02 (OH)2 and LiOH were mixed in a 1:1 molar ratio and subjected to a first heat treatment at 850°C for 8 hours in an oxygen atmosphere to obtain a composition of LiNi 0.75 Mn 0.23 Al 0.02 O2 and the average particle size (D 50 A composite oxide in the form of secondary particles having a particle size of 14 μm was produced.
[0122] After mixing aluminum sulfate with distilled water solvent, the prepared composite oxide was added and mixed for 20 to 60 minutes. At this time, the aluminum content in the aluminum sulfate was designed to be 1.0 mol% based on 100% by weight of the total metals excluding lithium in the final positive electrode active material. Next, manganese sulfate was added and mixed for 10 to 40 minutes. At this time, the manganese content in the manganese sulfate was designed to be 0.2 mol% based on 100% by weight of the total metals excluding lithium in the final positive electrode active material. After removing the solvent from the mixed solution and drying at 190°C, a second heat treatment was performed at 825°C for 8 hours in an oxygen atmosphere to prepare the final positive electrode active material.
[0123] 2. Manufacturing of lithium secondary batteries The positive electrode active material (98.5 wt%), polyvinylidene fluoride binder (1.0 wt%), and carbon nanotube conductive agent (0.5 wt%) were mixed to prepare a positive electrode active material layer slurry, which was then coated on an aluminum foil current collector, dried, and rolled to prepare a positive electrode. At this time, the loading level of the positive electrode active material layer was 10 mg / cm. 2 and the density of the final rolled cathode is about 3.4 g / cc.
[0124] A negative electrode active material layer slurry was prepared by mixing 97.5 wt% graphite negative electrode active material, 1.5 wt% carboxymethyl cellulose, and 1 wt% styrene butadiene rubber in an aqueous solvent. The negative electrode active material layer slurry was coated on a copper foil current collector, and then dried and rolled to prepare a negative electrode.
[0125] A polytetrafluoroethylene separator was used, and a lithium secondary battery was fabricated in a conventional manner using an electrolyte prepared by dissolving 1M LiPF6 in a solvent containing a mixture of ethylene carbonate and dimethyl carbonate in a volume ratio of 3:7.
[0126] Comparative Example 1 In the manufacture of the positive electrode active material, the Al, Mn coating process is not carried out, and LiNi 0.75 Mn 0.23 Al 0.02 A positive electrode active material and a lithium secondary battery were produced in substantially the same manner as in Example 1, except that the O2 composite oxide itself was used as the positive electrode active material.
[0127] Comparative Example 2 A positive electrode active material and a lithium secondary battery were manufactured in substantially the same manner as in Example 1, except that in the preparation of the positive electrode active material, only Al was dry-coated without Mn coating.
[0128] The Al dry coating method is as follows: 0.75 Mn 0.23 Al 0.02 The composite oxide in the form of secondary particles, which is O2, is mixed with aluminum oxide powder and heat-treated at 825°C for 8 hours in an oxygen atmosphere to obtain a dry-type Al-coated positive electrode active material.
[0129] Comparative Example 3 A positive electrode active material and a lithium secondary battery were manufactured in substantially the same manner as in Example 1, except that in the preparation of the positive electrode active material, only Al was wet-coated without Mn coating.
[0130] That is, after aluminum sulfate is mixed with a distilled water solvent, the composite oxide is added and mixed for about 20 to 60 minutes, the solvent is removed, the mixture is dried at 190°C, and a second heat treatment is performed at 825°C for 8 hours in an oxygen atmosphere to produce a cathode active material according to Comparative Example 3.
[0131] Comparative Example 4 A positive electrode active material and a lithium secondary battery were manufactured in substantially the same manner as in Example 1, except that in the preparation of the positive electrode active material, only Mn was wet-coated without Al coating.
[0132] That is, the composite oxide is added to a distilled water solvent, and manganese sulfate is added and mixed for about 10 to 40 minutes. Then, the solvent is removed, and the mixture is dried at 190°C. Then, a second heat treatment is performed at 825°C for 8 hours in an oxygen atmosphere to produce a cathode active material according to Comparative Example 4.
[0133] Evaluation example 1: Positive electrode active material analysis The positive electrode active material particles prepared in Example 1 were cut using a focused ion beam (FIB), and the cross section was subjected to SEM-EDS and HR-STEM analysis. Figure 5 is an SEM-EDS analysis image of the cross section of the positive electrode active material of Example 1, in which Mn is highlighted, and Figure 6 is an image of the same analysis in which Al is highlighted.
[0134] Referring to Figures 5 and 6, it can be seen that a first coating layer containing high density Al is formed with a uniform thickness on the surface of the core particle, and a second coating layer containing Mn is formed in the form of a film on the first coating layer.
[0135] FIG. 7 is an HR-STEM image of a cross section of the positive electrode active material of Example 1, showing that not only the core particle but also the first and second coating layers have a layered structure.
[0136] Evaluation example 2: Charge / discharge characteristics and high-temperature life characteristics The lithium secondary batteries prepared in Example 1 and Comparative Examples 1 to 4 were initially charged and discharged at a constant current of 0.2 C to 4.45 V and a constant voltage of 0.05 C at 25° C., and then discharged at 0.2 C to 3.0 V. The initial discharge capacities are shown in Table 1 below.
[0137] Next, the cycle of charging at 1.0C and discharging at 1.0C in the voltage range of 3.0V to 4.45V at 45°C was repeated 25 times or more, and the ratio of the 25-cycle discharge capacity to the initial discharge capacity was calculated and shown in Table 1 below as the high temperature life.
[0138] [Table 1]
[0139] Referring to Table 1, it can be seen that the lithium secondary battery of Example 1 achieves higher initial discharge capacity and life characteristics than those of Comparative Examples 1 to 4.
[0140] Although the preferred embodiments have been described in detail above, the scope of the present invention is not limited thereto, and various modifications and improvements made by those skilled in the art using the basic concepts defined in the claims also fall within the scope of the present invention. [Explanation of symbols]
[0141] 100: Lithium secondary battery 10: Positive electrode 11: Positive electrode lead tab 12: Positive terminal 20: Negative electrode 21: Negative electrode lead tab 22: Negative terminal 30: Separator 40: Electrode assembly 50: Case 60: Sealing material 70: Electrode tab 71: Positive electrode tab 72: Negative electrode tab
Claims
1. Core particles containing a layered lithium nickel-manganese composite oxide; a first coating layer located on the surface of the core particle and containing Al; and The positive electrode active material includes a second coating layer located on the first coating layer and containing Mn.
2. 2. The positive electrode active material according to claim 1, wherein in the layered lithium nickel-manganese composite oxide of the core particle, the nickel content is 60 mol% to 80 mol% relative to 100 mol% of all metals excluding lithium, and the manganese content is 10 mol% or more.
3. 2. The positive electrode active material according to claim 1, wherein the layered lithium nickel-manganese composite oxide of the core particle further contains aluminum, and the content of aluminum in the core particle is 1 mol % to 3 mol % relative to 100 mol % of all metals excluding lithium.
4. 2. The positive electrode active material according to claim 1, wherein the layered lithium nickel-manganese composite oxide of the core particle has a cobalt content of 0 mol % to 0.01 mol % relative to 100 mol % of all metals excluding lithium.
5. 2. The positive electrode active material according to claim 1, wherein the layered lithium nickel-manganese composite oxide of the core particle is represented by Chemical Formula 1. [Chemical formula 1] Li a1 Ni x1 Mn y1 Al z1 M 1 w1 O 2-b1 X b1 (In Chemical Formula 1, 0.9≦a1≦1.8, 0.6≦x1≦0.8, 0.1≦y1≦0.4, 0≦z1≦0.03, 0≦w1≦0.3, 0.9≦x1+y1+z1+w1≦1.1, and 0≦b1≦0.1; M 1 is one or more elements selected from B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W, Y, and Zr, and X is one or more elements selected from F, P, and S.
6. The positive electrode active material according to claim 1 , wherein the first coating layer and the second coating layer are in the form of a continuous film.
7. The thickness of the first coating layer is 5 nm to 40 nm; The positive electrode active material according to claim 1 , wherein the second coating layer has a thickness of 10 nm or less.
8. 2. The positive electrode active material of claim 1, wherein a ratio of a thickness of the second coating layer to a thickness of the first coating layer is less than 0.
5.
9. The Al content of the first coating layer is 0.1 mol % to 2 mol % based on 100 mol % of all metals excluding lithium in the positive electrode active material, 2. The positive electrode active material according to claim 1, wherein the Mn content of the second coating layer is 0.01 mol % to 1 mol % based on 100 mol % of all metals in the positive electrode active material excluding lithium.
10. The Al content of the first coating layer is 0.5 mol % to 1.5 mol % based on 100 mol % of all metals excluding lithium in the positive electrode active material, 2. The positive electrode active material according to claim 1, wherein the Mn content of the second coating layer is 0.05 mol % to 0.5 mol % based on 100 mol % of all metals in the positive electrode active material excluding lithium.
11. The positive electrode active material according to claim 1 , wherein a ratio of the Mn content of the second coating layer to the Al content of the first coating layer is less than 0.
5.
12. the first coating layer comprises aluminum oxide, lithium-aluminum oxide, or a combination thereof; 10. The cathode active material of claim 1, wherein the second coating layer comprises manganese oxide, lithium-manganese oxide, aluminum-manganese oxide, lithium-aluminum-manganese oxide, or a combination thereof.
13. The positive electrode active material according to claim 1 , wherein the first coating layer and the second coating layer have a layered structure.
14. The cathode active material of claim 13 , wherein the second coating layer further comprises a spinel structure.
15. The core particle is in the form of a secondary particle formed by agglomeration of a plurality of primary particles, The positive electrode active material of claim 1 , further comprising a grain boundary coating portion containing Al and located on a surface of a primary particle inside the secondary particle.
16. The positive electrode active material according to claim 15 , wherein the Al content in the grain boundary coating portion is less than the Al content in the first coating layer.
17. The average particle size (D 50 2. The positive electrode active material according to claim 1, wherein the thickness of the first electrode is 10 μm to 20 μm.
18. A layered nickel-manganese composite hydroxide and a lithium raw material are mixed and subjected to a first heat treatment to obtain a layered lithium nickel-manganese composite oxide; An Al raw material is added to an aqueous solvent, the lithium nickel-manganese composite oxide is added and mixed, and then an Mn raw material is added and mixed; and drying the resultant mixture and subjecting it to a second heat treatment.
19. The layered nickel-manganese composite hydroxide has a nickel content of 60 mol% to 80 mol%, a manganese content of 10 mol% or more, an aluminum content of 0 mol% to 3 mol%, and a cobalt content of 0 mol% to 0.01 mol%, relative to 100 mol% of the total metal. The method for producing a positive electrode active material according to claim 18.
20. The Al content in the Al raw material is 0.1 mol % to 2 mol % relative to 100 mol % of all metals excluding lithium in the positive electrode active material, The method for producing a positive electrode active material according to claim 18, wherein the Mn content in the Mn raw material is 0.01 mol % to 1 mol % relative to 100 mol % of all metals excluding lithium in the positive electrode active material.
21. The Al source includes aluminum nitrate, aluminum sulfate, aluminum carbonate, aluminum hydroxide, or a combination thereof; 20. The method of claim 18, wherein the Mn source comprises manganese nitrate, manganese sulfate, manganese carbonate, manganese hydroxide, or a combination thereof.
22. The method for producing a positive electrode active material according to claim 18, wherein the solution in which the Al raw material is added to the aqueous solvent has a pH of 1.5 to 3.
5.
23. The first heat treatment is carried out at 750°C to 950°C, The method for producing a positive electrode active material according to claim 18, wherein the second heat treatment is performed at 700°C to 850°C.
24. A positive electrode current collector, and a positive electrode active material layer located on the positive electrode current collector, The positive electrode active material layer comprises the positive electrode active material according to any one of claims 1 to 17.
25. The loading level of the positive electrode active material layer is 10 mg / cm 2 ~40mg / cm 2 25. The positive electrode of claim 24,
26. 25. The positive electrode of claim 24, wherein the positive electrode active material layer has a density of 3.3 g / cc to 3.7 g / cc.
27. The positive electrode according to claim 24 . a negative electrode, and A lithium secondary battery containing an electrolyte.
28. 28. The lithium secondary battery according to claim 27, having a charging voltage of 4.45 V or more.
Citation Information
Patent Citations
Li-ni composite oxide particle powder for nonaqueous electrolyte secondary battery, its manufacturing method, and nonaqueous electrolyte secondary battery
JP2008251532A
Lithium metal oxide cathode powder for high voltage lithium ion batteries
JP2018508943A